Photographs of all breeding sites of common guillemot (Uria aalge) 2014 in at Stora Karlsö in the Baltic Sea - Olsson, Olof (Stockholm University, 2017)
Complete description of the study that the photographs are part of is available in the following scientific publication:
Olsson, O. & Hentati-Sundberg, J. 2017. Trends and status of four seabird species at Stora Karlsö in the Baltic Sea. Ornis Svecica (2)

Purpose:

The purpose is that this documentation of photographs shall be available for future censuses of the common guillemots at Stora Karlsö

Fullständig beskrivning av studien som fotodokumentationen gäller finns i en vetenskaplig artikel med följande referens:
Olsson, O. & Hentati-Sundberg, J. 2017. Trends and status of four seabird species at Stora Karlsö in the Baltic Sea. Ornis Svecica (2)

Syfte:

Syftet är att denna fotodokumentation ska finnas tillgänglig för framtida inventeringar av sillgrisslorna på Stora Karlsö.
Fotodokumentation av samtliga häckningsplatser för sillgrissla (Uria aalge) under 2014 på Stora Karlsö i Östersjön
Keywords: animals; djur; zoology; zoologi; ornithology; ornitologi; birds; fåglar; wild animals; vilda djur; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Natural Sciences; Naturvetenskap